Coated electrospun polyamide-6/chitosan scaffold with hydroxyapatite for bone tissue engineering. (17th February 2021) - Niu, Xiaolian; Qin, Miao; Xu, Mengjie; Zhao, Liqin; Wei, Yan; Hu, Yinchun; Lian, Xiaojie; Chen, Song; Chen, Weiyi; Huang, Di
Abstract: Polyamide-6 (PA6) is a synthetic polymer that bears resemblance to collagen in its backbone and has excellent stability in human body fluid. Chitosan (CS) with the similar structure to that of the polysaccharides existing in the extracellular matrix (ECM), has a more suitable biodegradation rate for the formation of new-bone. Electrospun fiber have nanoscale structure, high porosity and large specific surface area, can simulate the structure and biological function of the natural ECM. To meet the requirements of mechanical properties and biocompatibility of bone tissue engineering, electrospun PA6/CS scaffolds were fabricated by electrospinning technology. The mineralized PA6/CS scaffolds were obtained through immersion in 1.5× simulated body fluid (1.5SBF), which allowed the hydroxyapatite (HA) layer to grow into the thickness range under very mild reaction conditions without the need of a prior chemical modification of the substrate surface. The results showed that electrospun PA6/CS fibrous scaffolds in the diameter range of 60–260 nm mimic the nanostructure of the ECM. The tensile strength and modulus of 10PA6/CS fibrous scaffolds reach up to 12.67 ± 2.31 MPa and 95.52 ± 6.78 MPa, respectively. After mineralization, HA particles uniformly distributed on the surface of PA6/CS fibrous scaffolds in a porous honeycomb structure, and the content of mineral was about 40%. In addition, cell culture study indicated that the mineralized PA6/CS composite scaffolds were non-cytotoxic, and had a good biocompatibility and an ability to promote MC3T3-E1 cell attachment and proliferation.